Violent crimes in native and foreign national offenders - Arbach, Karin (2014)
Although the foreign national population in Spanish prisons has doubled during the past decade from 22% to 44%, few studies have investigated the contribution of foreign nationals to criminality and their risk profiles compared to natives. The present paper compared rates of violent conviction in 917 native and 657 foreign national male offenders, and explored differences in risk factors for violence between groups using logistic regression, receiver operating characteristic (ROC) curve analysis, and positive and negative predictive values (PPV and NPV, respectively). Natives and foreign nationals showed no significant differences in the rate of violent conviction (19.6% vs. 17.2%, respectively). However, when multivariate models were developed to predict violence in the samples using logistic regression, between-group differences in the risk profiles of violent and non-violent offenders were found. Implications of the findings for research, public policy and risk management were explored.